Pengaruh Pelatihan dan Komunikasi Terhadap Kinerja Karyawan Desa Visesa Ubud Resort - Widiana, I Wayan Adi; Mekarini, Ni Wayan; Suryaningsih, Ida Ayu Anggreni (Universitas Triatma Mulya, 2022)
The study entitled the Effect of Training and Communications on the Vessel's Village of Vimad Resort was intended to learn about the partial and simpliting effects of employee performance. The type of data used in research is quantitative data and qualitative analysis, the sample analysis used which is purposive sampling and random sampling or random sample with the number of responders obtained by 61 responders. The study that authors use is documentation, question, analysis is a qualification, analysis used in the classic analysis, the correlation analysis of liniganda, and testing (uji-t dan uji f) with the help of the IBM SPSS static 26 program is producing. Studies produce 3 knots that are (a) Training has a positive and significant effect on employee performance, meaning that every increase in communication by 1 unit leads to a 0.634 employee performance in the village of Visessa Resort, and (c) Training and communication have a positive effect and significant impact on employee performances, meaning that if training (X1 and Communications (X2) are raised together by 1 then Kinerja (Y) will increase by 0.708 (0.074 + 0.634) in Desa Visesa Ubud Resort.